Implementation of Call Center Service 112 as Public Service Innovation in Ciamis Regency - Irgi Aura Aprilia; Esa Nursafitri; Refansyah Mukti; Ii Sujai (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This research aims to analyze the implementation of the Call Center 112 service as an innovation in improving public services in Ciamis Regency. This service was launched in response to the mandate of Law Number 14 of 2008 on Public Information Disclosure, which encourages public services to be available 24 hours, both in emergency and non-emergency situations. The Call Center 112 not only serves emergency reports but also requests for general information related to public services such as mobile vehicle tax services (Samsat) and police administration. In its implementation, this service collaborates with a third party, namely PT Digital Sandi Informasi, and is integrated with various agencies such as the Police Department, Fire Department, and Search and Rescue. However, there are several challenges such as limited infrastructure, technical disruptions of the application, and a high number of false reports from the public. Through the strengthening of SOPs, training of human resources, and integration into the SP4N Lapor platform, it is hoped that the Call Center 112 can become an effective and sustainable model of public service innovation in the future.